LncRNA KCNQ1OT1 inhibits the radiosensitivity and promotes the tumorigenesis of hepatocellular carcinoma via the miR-146a-5p/ACER3 axis. Issue 19 (1st October 2020) - Yang, Ganghua; Zhou, Lijing; Xu, Qinhong; Meng, Fandi; Wan, Yong; Meng, Xiankui; Wang, Lin; Zhang, Lei
ABSTRACT: Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related death, and radiotherapy is currently one of the main treatments. Long non-coding RNAs (lncRNAs) are associated with the radiosensitivity and tumorigenesis of HCC. However, the role and molecular mechanism of potassium voltage-gated channel subfamily Q member 1 overlapping transcript 1 (KCNQ1OT1) in HCC are still unclear. The relative expression of KCNQ1OT1, microRNA-146a-5p (miR-146a-5p) and alkaline ceramidase 3 (ACER3) was quantified by quantitative real-time polymerase chain reaction (qRT-PCR). Cell proliferation was measured by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) assay. Clonogenic assay was used to assess the radiosensitivity of cells. Cell apoptosis and metastasis were evaluated by flow cytometry and transwell assays, respectively. The protein levels of apoptosis markers, metastasis markers and ACER3 were detected by western blot (WB) analysis. The relationship between miR-146a-5p and KCNQ1OT1 or ACER3 was determined by dual-luciferase reporter assay. Additionally, animal experiments were carried out to explore the effect of KCNQ1OT1 silencing on HCC tumor growth in vivo . KCNQ1OT1 was highly expressed in HCC, and its knockdown hindered the proliferation and metastasis, while increased the radiosensitivity and apoptosis of HCC cells. MiR-146a-5p could interact with KCNQ1OT1, and its inhibition reversed the effects of silenced-KCNQ1OT1 on the radiosensitivity and tumorigenesis of HCC cells. Besides, ACER3 was a target of miR-146a-5p, and its overexpression inversed the effects of miR-146a-5p mimic on the radiosensitivity and tumorigenesis of HCC cells. The expression of ACER3 was regulated by KCNQ1OT1 and miR-146a-5p. Furthermore, KCNQ1OT1 also could reduce the growth of HCC by regulating the miR-146a-5p/ACER3 axis in vivo . Our study suggested that KCNQ1OT1 improved ACER3 expression to regulate the radiosensitivity and tumorigenesis of HCC through sponging miR-146a-5p, indicating that KCNQ1OT1 might be a new therapeutic target for HCC.